A INSERÇÃO DE CONCEITOS CIENTÍFICOS NO COTIDIANO ESCOLAR - Manechine, Selma Rosana Santiago [UNESP]; Gabini, Wanderlei Sebastião [UNESP]; Caldeira, Ana Maria De Andrade [UNESP]; Diniz, Renato Eugênio Da Silva [UNESP] (Faculdade de Educação da Universidade Federal de Minas Gerais, 2006)
The present study detaches the valuation of the learning process, emphasizing the integration of disciplines and the contextualization of the teaching process. The integrator instrument of this study was the production of some essential oils, that involved scientific concepts related to Chemistry, Mathematics, Biology and Geography. After the students had answered to a previous questionnaire about a company, they were invited to visit the its installations, with they teachers and guided to take some informations about a kind of substance, named alfabisabolol, like its raw material exploration, production and trade. It was noticed a great devotion of the students during the activities developed on this project, probably because the subjects were part of their personal, social and cultural reality.

O presente estudo destaca a valorização do processo de aprendizagem enfatizando a integração de disciplinas e a contextualização do ensino. O instrumento integrador desse estudo foi a produção de óleos essenciais, envolvendo conceitos científicos relacionados às disciplinas de Química, Matemática, Biologia e Geografia. Após responderem a um questionário prévio sobre determinada empresa, os alunos visitaram-na, juntamente com os professores, levantando dados a respeito da substância alfabisabolol, da exploração da matéria-prima, da produção e da comercialização. Percebeu-se um destacado envolvimento desses alunos nas atividades desenvolvidas durante o Projeto em virtude dos conceitos tratados integrarem-se à sua realidade pessoal, social e cultural.
The insertion of scientific concepts in the daily pertaining to school
Keywords: high school teaching; interdisciplinarity; teaching of scientific concepts.; ensino médio; interdisciplinaridade; ensino de conceitos científicos.